Ecofriendly management of cutworm, Agrotis ipsilon and cabbage butterfly, Pieris brassicae in cabbage - Rameash, K; Kumar, Ashok; Kalita, H; Avasthe, R K (Indian Journal of Plant Protection, 2020)
In cabbage, field studies were conducted to evaluate the bioefficacy of entomopathogenic microbes, botanical pesticides, insect growth regulators and natural insecticides in the management of cutworm, Agrotis ipsilon and cabbage butterfly, Pieris brassicae. Application of emamectin benzoate (0.002%) significantly reduced damage of A. ipsilon, while spinosad (0.002%) and emamectin benzoate (0.002%) provided a superior control over the larval population of P. brassicae. The biopesticides were found to be significantly superior to the standard check, chlorpyrifos (0.05%) in controlling both the insect pests. Both the pesticides recorded a significant increase in marketable yield of cabbage at harvest.